CHARACTER EDUCATION MODEL IN BUILDING THE CHARACTER OF CHILDREN IN SPECIAL CHILDREN GUIDANCE INSTITUTIONS (LPKA) - Sitepu, Karina Wenita; Biafri, Vivi Sylviani (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This article explores the implementation of character education models in Pembinaan Institutions Special for Children (LPKA) as an essential approach in rehabilitating children in conflict with the law. In the face of complex social and emotional challenges, children in LPKA often experience behavioral and emotional issues that require special attention. Character education serves as both a tool to transform negative behaviors into positive ones and a means to build a strong and healthy personality foundation. The model emphasizes the inculcation of universal values such as honesty, discipline, responsibility, empathy, and cooperation, tailored to the unique needs of these children within the Indonesian cultural context. A supportive learning environment and varied instructional methods, such as experiential learning and project-based activities, are highlighted as key elements in engaging children and fostering their understanding of moral values. The article also discusses the importance of ongoing evaluation and staff training to ensure the program's success. Additionally, the article identifies both supporting and inhibiting factors in the implementation of character education in LPKA, including the need for positive environments, family participation, and sufficient resources, while addressing challenges such as social stigma, emotional instability, and administrative issues. Ultimately, the character education model aims to rehabilitate children, equipping them with moral integrity and resilience as they reintegrate into society after their time in LPKA. Keywords: Character Education; Juvenile Rehabilitation; Moral Values